CHALLENGES IN CONSECUTIVE TRANSLATION IN POLITICAL DISCOURSE - Haytboyeva , Gulhayo Shukurillo qizi (Educational Research in Universal Sciences, 2023)
Consecutive translation in political discourse presents a formidable task, characterized by a myriad of challenges rooted in linguistic, cultural, and contextual complexities. This study investigate the unique hurdles faced by interpreters in navigating the intricacies of political communication. Analyzing the dynamic nature of political discourse, we explore the role of rhetorical devices, cultural references, and non-verbal cues, highlighting their impact on successful interpretation. Cultural considerations emerge as a critical factor, demanding interpreters possess profound cultural awareness to navigate political language’s nuances. The study scrutinizes potential pitfalls arising from cultural disparities, emphasizing the challenge of preserving intended connotations while maintaining political neutrality. The study further examines the influence of rapidly evolving political contexts on consecutive translation. Real-time developments demand interpreters adapt to changing scenarios, requiring strategies to uphold message integrity amidst temporal dynamics. Additionally, the technological dimension is explored, assessing the effectiveness of digital tools and real-time translation technologies, juxtaposed with ethical considerations.